Case Report: Conservative Treatment of Adolescent Idiopathic Scoliosis Can Alter the Perception of Verticality. A Preliminary Study - Zagalaz-Anula, Noelia; León-Morillas, Felipe; Andradre-Ortega, Juan Alfonso; Ibáñez-Vera, Alfonso Javier; de Oliveira-Sousa, Silvana Loana; Lomas-Vega, Rafael (Frontiers in Pediatrics, 2021)
Adolescent idiopathic scoliosis (AIS) is a lateral curvature of the spine of at least 10° Cobb's angle of unknown etiology. Some studies have found that patients with AIS have a Visual Verticality (VV) perception similar to healthy controls. This study aimed to analyze VV perception and postural balance differences in patients with AIS depending on the management, either based on observation or conservative treatment. Eighteen patients with AIS were included in this study. Nine patients were managed based on observation. The other nine underwent conservative treatment, such as bracing or exercise. Subjective Visual Vertical (SVV) and posturographic parameters were measured and analyzed. In the SVV test, patients who underwent treatment showed poor constant error in absolute values and mean absolute error, with statistically significant differences (p < 0.05). Only the Romberg Quotient for sway area was within the limits of statistical significance for posturographic parameters, with a lower value for patients under observation. This study found worse perception of verticality in patients receiving some type of conservative treatment than patients receiving only observation; whereas posturography showed similar values in both observation and treatment groups. Our results can be interpreted as the effect of treatment on the previous verticality perception adapted to the curvature.